Populism 2.0, Digital Democracy and the New ‘Enemies of the People’ - Momoc, Antonio (Communication Today, 2018)
Like in many other Central and Eastern European countries, in 2016, Romanian populist parties were voted by the ‘silent’ citizens, by those feeling deprived and not represented properly. Shortly before that, in 2015, the tragic Colectiv nightclub fire had given birth to a new party: Save Romania Union (USR) that promotes a populist discourse on the ‘corrupt elite’ versus the ‘pure people’. At the beginning, however, the new party did not disseminate messages specific to then ationalist or radical right-wing populists. Another party, endorsed by a news television channel Romania TV, almost succeeded at overpassing the electoral threshold in the 2016 parliamentary election: United Romania Party (PRU) used xenophobic and anti-EU messages during the 2016 general election campaign. My hypothesis is that the extremist electoral messages, the expressions of hatred towards foreigners and Western businessmen or the EU institutions were spread through social networks. Using a content analysis, I shall verify the extent to which the official Facebook pages of the Social Democratic Party (PSD, the direct successor of the Romanian Communist Party), the United Romania Party (PRU) and the Save Romania Union (USR) reflected the antagonism of the ‘pure’ people versus the ‘corrupt’ elite and I shall reveal who these parties identified as the so-called ‘people’s enemies’.